A new infaunal species of the genus Enosteoides Johnson, 1970 (Crustacea: Decapoda: Anomura: Porcellanidae) from Okinawa, southwestern Japan - Osawa, Masayuki; Nakajima, Hiroki; Hamamoto, Kohei (Zootaxa, 2022)
A new porcellanid species of the genus Enosteoides Johnson, 1970 is described on the basis of a single specimen collected from the burrow of an unidentified snapping shrimp of the genus Alpheus Fabricius, 1798, on the subtidal coarse sediment in Okinawa Island, Ryukyu Islands, southwestern Japan. Enosteoides lapis n. sp. is similar to E. melissa (Miyake, 1942) and E. philippinensis Dolorosa & Werding, 2014 in the general morphology of the frontal region of the carapace, third thoracic sternite, and ambulatory legs, but is distinguished from both by the dorsal surface of the carapace being more strongly uneven, as well as by the absence of dense plumose setae on the lateral margins of the carapace, anterodorsal surfaces of the chelae, and anterior and posterior margins of the ambulatory meri.